The Influence of Liquidity, Leverage, Company Growth and Profitability on Dividend Policy in Manufacturing Companies on The Indonesia Stock Exchange for The Period 2017 - 2019 - Fahad Rohma Dika; Muhammad Rijalus Sholihin; Moh. Hudi Setyo Bakti (International Journal of Accounting and Management Research, 2023)
The purpose of this study is to test and analyze the effect of liquidity, leverage, company growth and profitability on dividend policy. This research is quantitative research. The research objects used in this study are current ratio (CR), debt to equity ratio (DER), growth, and return on assets (ROA), on the dependent variable, namely dividend policy. The type of data in this study is secondary data sourced from annual financial reports published through the official website on the Indonesian stock exchange. The population used is manufacturing companies on the Indonesian stock exchange. Sampling this study using purposive sampling with a total sample of 20 companies. The method used in quantitative research, especially quantitative analytics is the deductive method. The technique in this study uses multiple linear analysis. The results of this study indicate that the curent ratio has no effect on the dividend payout ratio in manufacturing companies on the Indonesian stock exchange for the period 2017 - 2019.